Closed Synthetic Cycle for Nickel-Based Dihydrogen Formation - Hosseinmardi, Soosan; Scheurer, Andreas; Heinemann, Frank Wilhelm; Marigo, Nicola; Munz, Dominik; Meyer, Karsten (Chemistry - A European Journal, 2023)
Dihydrogen evolution was observed in a two-step protonation reaction starting from a Ni0 precursor with a tripodal N-heterocyclic carbene (NHC) ligand. Upon the first protonation, a NiII monohydride complex was formed, which was isolated and fully characterized. Subsequent protonation yields H2 via a transient intermediate (INT) and an isolable NiII acetonitrile complex. The latter can be reduced to regenerate its Ni0 precursor. The mechanism of H2 formation was investigated by using a deuterated acid and scrutinized by 1H NMR spectroscopy and gas chromatography. Remarkably, the second protonation forms a rare nickel dihydrogen complex, which was detected and identified in solution and characterized by 1H NMR spectroscopy. DFT-based computational analyses were employed to propose a reaction profile and a molecular structure of the Ni−H2 complex. Thus, a dihydrogen-evolving, closed-synthetic cycle is reported with a rare Ni−H2 species as a key intermediate.
CRIS-Team Scopus Importer:2023-10-20
Keywords: H; NHC; nickel complexes; nickel dihydrogen; nickel hydride

Evaluation of Manganese Cubanoid Clusters for Water Oxidation Catalysis: From Well-Defined Molecular Coordination Complexes to Catalytically Active Amorphous Films - Hosseinmardi, Soosan; Scheurer, Andreas; Heinemann, Frank Wilhelm; Kuepper, Karsten; Senft, Laura; Waldschmidt, Pablo; Ivanovic-Burmazovic, Ivana; Meyer, Karsten (Chemsuschem, 2021)
With a view to developing multimetallic molecular catalysts that mimic the oxygen-evolving catalyst (OEC) in Nature's photosystem II, the synthesis of various dicubanoid manganese clusters is described and their catalytic activity investigated for water oxidation in basic, aqueous solution. Pyridinemethanol-based ligands are known to support polynuclear and cubanoid structures in manganese coordination chemistry. The chelators 2,6-pyridinedimethanol (H2L1) and 6-methyl-2-pyridinemethanol (HL2) were chosen to yield polynuclear manganese complexes; namely, the tetranuclear defective dicubanes [MnII2MnIII2(HL1)4(OAc)4(OMe)2] and [MnII2MnIII2(HL1)6(OAc)2] (OAc)2⋅2 H2O, as well as the octanuclear-dicubanoid [MnII6MnIII2(L2)4(O)2(OAc)10(HOMe/OH2)2]⋅3MeOH⋅MeCN. In freshly prepared solutions, polynuclear species were detected by electrospray ionization mass spectrometry, whereas X-band electron paramagnetic resonance studies in dilute, liquid solution suggested the presence of divalent mononuclear Mn species with g values of 2. However, the magnetochemical investigation of the complexes’ solutions by the Evans technique confirmed a haphazard combination of manganese coordination complexes, from mononuclear to polynuclear species. Subsequently, the newly synthesized and characterized manganese molecular complexes were employed as precursors to prepare electrode-deposited films in a buffer-free solution to evaluate and compare their stability and catalytic activity for water oxidation electrocatalysis.
CRIS-Team Scopus Importer:2021-10-08
Keywords: cubanes; electrocatalysis; electrodeposition; manganese; water splitting